The Influence of Talent Management and Integrity Zones on Organizational Performance at the BPKP Representative Office of Riau Islands Province - Mindarto Totok Oktaruna; Lijan Poltak Sinambela; Zainur Hidayah; Martino Wibowo (AIBPM Publisher, 2022)
The aims of studi are to examine the effect of talent management and zone of integrity on organizational performance. This research was conducted at BPKP of the Riau Islands Province. The research population is all employees of the BPKP Representative Office of the Riau Islands Province. The research sample was 40 employees with the sampling technique was simple random sampling. The test results show that there is a positive and significant influence of talent management on organizational performance of 6.838 and a significant value of 0.000. The positive and significant influence of the integrity zone on organizational performance is 1,536 and a significant value is 0.000. The simultaneous influence of talent management and integrity zone is positive and significant on organizational performance of 23,376 and a significant value of 0.000.Keywords: Talent Management, Integrity Zone, Organizational Performance, Corruption Free Area, Government Governance.